If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(7x-1=8x-10)
We move all terms to the left:
(7x-1-(8x-10))=0
We calculate terms in parentheses: +(7x-1-(8x-10)), so:We get rid of parentheses
7x-1-(8x-10)
determiningTheFunctionDomain 7x-(8x-10)-1
We get rid of parentheses
7x-8x+10-1
We add all the numbers together, and all the variables
-1x+9
Back to the equation:
+(-1x+9)
-1x+9=0
We move all terms containing x to the left, all other terms to the right
-x=-9
x=-9/-1
x=+9
| x+(x+0.13)+(x+0.10)=5200 | | x+(x+0.13)+(x+0.13)=5200 | | 8x+18-7x=-3-11 | | 45=3,8x | | x-1(1/2)=2(1/3) | | x+20+2x= | | (5x-7=4x+6) | | (8x-9=6x-7) | | x—5=8—2(x+2) | | 10(s-9)=197 | | 10x—18=3+8x | | 136=8(-1+4x) | | Y=2x²-12x+16 | | O=2x²-12x+16 | | F(x)=2x^2-15x+7 | | 25x+20x=420 | | 4-2c=10-8c= | | 2y/9=2 | | (3-8c)1.5=4.5-12c | | (8x+19=59) | | (9x+2=7x+18) | | 20=-4.9x^2-42x+100 | | x*2x=392 | | x+x+42=300 | | Z^4+13z^2+36=0اعدادمركبه | | (5x+19=6x+1) | | (7x+3=8x+1) | | (6x-8=5x+14) | | (5x+2=4x+6) | | 27+3x=x+93 | | B(40)=15.00-0.09x | | k=49÷7 |